Partial characterization and enrichment of a membrane-bound sialidase specific for gangliosides from human brain tissue - Kopitz, Jürgen; Sinz, Karin; Brossmer, Reinhard; Cantz, Michael (EJB, 1997)
Gangliosides, constituents of surfaces of vertebrate cells, modulate important cellular functions. Ganglioside-specific sialidases that possibly control these processes have been observed in a number of tissues, but their characterization has proved difficult due to their low abundance and lability. Here we describe the partial isolation and characterization of a ganglioside sialidase from human brain grey matter. After membrane extraction with octylglucoside, the enzyme was purified about 1300-fold by ion-exchange, affinity and gel-permeation chromatographies. Although PAGE still showed several protein bands, specific photoaffinity labelling with iodinated 5-Af-acetyl-9-(4-azidosalicoylamido)-2,9-dideoxy-2,3-didehydroneuraminic acid identified a single polypeptide of 60 kDa likely to contain the active site of the sialidase. In the presence of 0.4% octylglucoside, the purified sialidase desialylated gangliosides GM3, GD1a, GD1b and GT1b, but was inactive towards GM1, GM2, colominic acid, sialyl-(α2-3)-lactose, 2-(4-methylumbelliferyl)-neuraminate, or the glycoprotein fetuin. The ganglioside sialidase activity was strongly inhibited by 2-deoxy-2,3-didehydro-N-acetylneuraminic acid, heparin and heparan sulfate. Because of its substrate and inhibitor profiles, the purified enzyme resembles the activity characterized previously in the plasma membrane of human neuroblastoma cells, but is distinct from a lysosomal activity. The purified brain sialidase thus appears to function in the selective desialylation of gangliosides with terminal sialic acid residues.
Elektronische Reproduktion der Druck-Ausgabe 16. Juli 2004
Gesehen am 01.07.2024